Uso de los antibióticos en síndrome diarreico agudo en pacientes pediátricos que acuden al Centro de Salud de Catamayo - Vélez Guerrero, Cristina Lucía (2014)
A qualitative and quantitative descriptive prospective cross-sectional study was conducted conducted June - December 2013; aimed at determining the use of antibiotics in pediatric patients diagnosed with acute diarrheal disease (ADD), treated at the Health Center Catamayo to establish whether they are subject to MSP protocols, PAHO, WHO in order to strengthen or promote wise use of those. Specific way: Knowing, quantitatively antibiotic use in different clinical forms of acute diarrheal disease. Identify if you are applying the protocol of the Ministry of Health on the use of antibiotics in the Health Center. Establish the use of Oral Rehydration Salts in the clinical forms of acute diarrheal disease. Determine the knowledge of health workers on pediatric doses recommended in national and international guidelines antibiotics. Encourage the use of the protocols of the Ministry of Public Health in the institution. The results found were: the use of antibiotics in clinical forms of EDA in a high percentage, the most frequent was trimethoprim-sulfamethoxazole in 70%; amoxicillin with 20% and 10% for worming. In the clinical records showed that 92% do not work according to MSP protocols for prescribing antibiotics and rehydration and 8% of the case if applied. Oral rehydration salts were used in 75% of cases and 25% other. 86% of physicians are aware of the recommended dose protocols. Therefore it can be concluded that the study was evident in medical records irrational use of antibiotics in the clinical forms of diarrhea in pediatric patients, carriers of EDA, because they are not subject to the protocols of the Ministry of Health public. Keywords: acute diarrheal disease (ADD) Protocols.